The worlds of limited-edition books (Arthur Clarke, Robert Heinlein, Wojciech Kajtoch, Stanisław Lem) - D.E. Martynov (Ученые записки Казанского университета: Серия Гуманитарные науки)
This paper reviews four books, all dedicated to the study of the science fiction genre and the biography of science-fiction writers. They were published in Russian in an extremely limited number. These books include a collection of articles by Wojciech Kaitoch, biographies of Arthur Clarke and Robert Heinlein written by Neil Mcaleer and William H. Patterson, respectively, as well as a biography of Stanisław Lem compiled by his son Tomasz. The authors of all biographies come from fundamentally important circumstances in the lives of the writers. The main approach to exploring the biographies under consideration is annual chronicle, which allows getting involved in the most diverse materials. For American biographers, a very important part of the biography is also sexual orientation and preferences. On the contrary, the Polish literary critic W. Kaitoch uses the modern methods in his literary research and turns towards the biographical approach only when there is no way to otherwise explain the features of the analyzed text. W. Kaitoch is skeptical of the idea about any possibility of revealing the author’s intention. Based on the obtained results, it was concluded that, under the conditions of media sphere dominance, specialized limited-edition publications in the field of the humanities are of interest to an extremely small number of specialists and literary fans.